Strategi Pembelajaran Problem Based Learning dalam Meningkatkan Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran SKI - Diajeng Juwita Ningrum; Moch. Chotib; Supriadi Supriadi (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Critical thinking skills are one of the important skills to develop in the learning process, including in the subject of Islamic Cultural History (SKI). However, SKI learning is often still centered on the teacher and does not involve students actively. Therefore, a learning strategy is needed that can stimulate student participation and critical thinking. This influence aims to explore the application of the Problem Based Learning (PBL) learning strategy in improving students' critical thinking skills in the subject of Islamic Cultural History (SKI) at Madrasah Aliyah Al Huda Banyuwang. This research uses a qualitative method with a case study approach. Data collection techniques were carried out through participatory observation and semi-structured interviews with research subjects consisting of SKI teachers, Deputy Principal for Curriculum, and class X students. The research results show that the application of PBL strategies significantly improves students' critical thinking abilities. They are able to analyze information in depth, evaluate various views, and convey arguments supported by valid data. Challenges in implementing PBL include limited learning time and teacher skills in implementing these strategies. This research concludes that PBL can be an effective learning strategy in improving students' critical thinking skills in SKI subjects at Madrasah Aliyah Al Huda Banyuwangi. This research recommends teacher training related to PBL as well as school policy support for its optimal implementation.